2002
DOI: 10.1002/ijc.10576
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CD40 expression and CD40‐mediated dendritic cell function by tumor‐derived IL‐10

Abstract: As CD40 plays a key role in both antitumor immunity and DC maturation, we have studied the regulation of its expression during DC hematopoiesis (dendropoiesis) in vitro and in vivo in the tumor microenvironment. Using MC38 colon adenocarcinoma tumor models, we have demonstrated that DCs generated in vitro from bone marrow precursors obtained from tumor-bearers have significantly lower expression of CD40 molecules compared to DCs generated from tumor-free mice. Furthermore, CD40 expression on DCs isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
35
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 58 publications
11
35
0
3
Order By: Relevance
“…However, the mechanism on how CD40 was involved in the process remained to be further investigated. Recent data showed that down-regulation of CD40 on DC cell surface and low-level CD40L on T cell surface of patients with pancreatic cancer impaired the function of DC cells, which was closely associated with the immunosuppressive status of cancer patients (26,27). Therefore, CD40 may be a valuable marker to predict the malignancy, invasive and metastatic potential and prognosis in pancreatic cancer patients.…”
Section: Discussionsupporting
confidence: 44%
“…However, the mechanism on how CD40 was involved in the process remained to be further investigated. Recent data showed that down-regulation of CD40 on DC cell surface and low-level CD40L on T cell surface of patients with pancreatic cancer impaired the function of DC cells, which was closely associated with the immunosuppressive status of cancer patients (26,27). Therefore, CD40 may be a valuable marker to predict the malignancy, invasive and metastatic potential and prognosis in pancreatic cancer patients.…”
Section: Discussionsupporting
confidence: 44%
“…Finally, if all the antitumor effects of CD40 were dependent on interaction with CD40L-mediated T cell activation, no antitumor effect would be observed in mice or human subjects lacking (or expressing less) CD40L or expressing nonfunctional mutant CD40L. In addition, impaired antitumor immune responses were associated with reduced expression of CD40L on T cells or CD40 on DC (21)(22)(23). The functional changes that occurred in those DC or T cells due to low CD40 or CD40L expressions are not yet understood.…”
supporting
confidence: 40%
“…Tumour cells are known to exert a range of suppressive effects on DC via secretion of cytokines such as IL-10, IL-6, VEGF and M-CSF, or via cell surface interactions. [12][13][14][15] Although Mel888 secrete IL10, the suppression of DC activation was not IL-10 mediated in these experiments, since levels of secretion were similar from fusing and nonfusing tumour cells, and the addition of soluble IL-10 blocking receptors was unable to lift this suppression. …”
Section: Discussionmentioning
confidence: 41%